Fatty acid uptake in Trypanosoma brucei: Host resources and possible mechanisms - Poudyal, Nava Raj; Paul, Kimberly S. (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma brucei spp. causes African Sleeping Sickness in humans and nagana, a wasting disease, in cattle. As T. brucei goes through its life cycle in its mammalian and insect vector hosts, it is exposed to distinct environments that differ in their nutrient resources. One such nutrient resource is fatty acids, which T. brucei uses to build complex lipids or as a potential carbon source for oxidative metabolism. Of note, fatty acids are the membrane anchoring moiety of the glycosylphosphatidylinositol (GPI)-anchors of the major surface proteins, Variant Surface Glycoprotein (VSG) and the Procyclins, which are implicated in parasite survival in the host. While T. brucei can synthesize fatty acids de novo, it also readily acquires fatty acids from its surroundings. The relative contribution of parasite-derived vs. host-derived fatty acids to T. brucei growth and survival is not known, nor have the molecular mechanisms of fatty acid uptake been defined. To facilitate experimental inquiry into these important aspects of T. brucei biology, we addressed two questions in this review: (1) What is known about the availability of fatty acids in different host tissues where T. brucei can live? (2) What is known about the molecular mechanisms mediating fatty acid uptake in T. brucei? Finally, based on existing biochemical and genomic data, we suggest a model for T. brucei fatty acid uptake that proposes two major routes of fatty acid uptake: diffusion across membranes followed by intracellular trapping, and endocytosis of host lipoproteins.